The Influence of Business Communication and Social Media on Online Shop Business - Heti Nubila; Baldi Anggara; Hairun Nisa; Hidayani, Hidayani (Penerbit dan Percetakan CV. Picmotiv, 2025)
This study aims to analyze the influence of business communication and social media usage on the performance of online shop businesses, focusing on operational efficiency, sales growth, and customer loyalty. The benefit of this study is to provide insights for online business owners about the importance of effective business communication and the utilization of social media to strengthen customer relationships and improve business performance. The method used is a quantitative approach, with data collection through surveys from owners and managers of online shops that actively use social media in Indonesia. The data obtained were analyzed using descriptive and regression statistical techniques to determine the relationship between business communication and social media usage on sales and customer loyalty. The results of the study show that good business communication, especially internal communication, significantly influences operational efficiency and customer satisfaction. In addition, the creative and interactive use of social media has been proven to increase sales by expanding market reach and improving customer engagement. The combination of both also contributes to increasing customer loyalty, where businesses that effectively manage both aspects have more loyal customers and are more likely to make repeat purchases.